Need Assessment Pembinaan Ekstrakurikuler Kemahasiswaan di Perguruan Tinggi - Merinda Noorma Novida Siregar; Rizki Oktavianto (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Extracurricular activities play an important role in supporting intracurricular and co-curricular activities in realizing quality college graduate output. Student extracurricular coaching in the era of Merdeka Belajar Kampus Merdeka (MBKM) faces several challenges ranging from the demands of student ranking to the demands of the world of work skills. The research aims to determine the need for extracurricular student development in higher education, which includes: 1) How is the implementation of student extracurricular coaching; 2) Obstacles faced by students in the implementation of extracurricular activities; 3) The needs of students to support student extracurricular activities. This research is exploratory descriptive research with a questionnaire instrument for data collection. The data analysis technique uses qualitative and quantitative descriptive analysis. The results showed: 1) The implementation of student extracurricular coaching is generally good; 2) Supporting facilities and student services are obstacles faced by students; 3) Students need supporting facilities, especially sports facilities and excellent service in student services. This research has a theoretical contribution to expanding the study of extracurricular student affairs in higher education. In addition, the results of this study are able to make a practical contribution as a basis for developing a model for fostering extracurricular student affairs in higher education.